Global Economic Uncertainties and Southeast Asian Economies - Chirathivat, Suthiphand (Book collections on Project MUSE., 2015)
Ihe aftermath of the global economic breakdown in 2008-9 underscores the risks facing Southeast Asia's growth prospects. Although the region has demonstrated exceptional resilience to external shocks emanating from economic powerhouses around the globe, Southeast Asia is in dire need of an optimal policy mix of macroeconomic and trade policy measures that differ by country, underpin domestic demand, and revive domestic economies. This book offers in-depth, region-specific economic policy discourse that illuminates how a policy push is at work in the region, and sheds light on room for strength.